2021
DOI: 10.1101/2021.06.09.21258495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cigarette Smoking-Associated Isoform Switching and 3’ UTR Lengthening Via Alternative Polyadenylation

Abstract: Cigarette smoking accounts for approximately one in five deaths in the United States. Previous genomic studies have primarily focused on gene level differential expression to identify related molecular signatures and pathways, but the genome-wide effects of smoking on alternative isoform regulation and posttranscriptional modulation have not yet been described. We conducted RNA sequencing (RNA-seq) in whole-blood samples of 454 current and 767 former smokers in COPDGene Study. We assessed the association of cu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Data. The RNA-seq data in whole-blood samples on 454 current and 767 former smokers were accessed from the Gene Expression Omnibus (GEO) database under the accession number GSE171730 [8]. We separated the samples into two classes based on their smoking history: current smokers and former smokers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data. The RNA-seq data in whole-blood samples on 454 current and 767 former smokers were accessed from the Gene Expression Omnibus (GEO) database under the accession number GSE171730 [8]. We separated the samples into two classes based on their smoking history: current smokers and former smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, gene expression alterations are important for smoking response. Considering that alternative splicing is applied by up to 95% of human genes for producing proteins with different functions, a recent study has focused on identifying smoking-associated isoforms and found that 3 ′ UTR lengthening was widely associated with cigarette smoking [7,8]. A total of 945 differentially expressed isoforms were identified in this study by using the classic statistic method.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation